Essays on Research Methodology - Hegde, Dinesh S (Springer, 2015)
The book presents a collection of essays addressing a perceived need for persistent and logical thinking, critical reasoning, rigor and relevance on the part of researchers pursuing their doctorates. Accordingly, eminent experts have come together to consider these significant aspects of the research process, which result in different knowledge claims in different fields or subject areas. An attempt has been made to find a common denominator across diverse management disciplines, so that the broadest range of researchers can benefit from the book. The topics have been carefully chosen to cover problem formulation, contextualizing, soft & hard modeling, qualitative and quantitative analysis and ethical issues, in addition to the design of experiments and survey-based research.